ANALYSIS OF ECONOMIC GROWTH AND UNEMPLOYMENT AS DETERMINING FACTORS OF POVERTY IN SOUTHEAST SULAWESI PROVINCE - Dewangga, Puspa; Saenong, Zainuddin; Samrin, La Ode Muhammad Arfan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study examines the impact of economic growth and the open unemployment rate on poverty levels in Southeast Sulawesi Province during the period 2005 to 2024. This study embraced a quantitative approach, drawing on secondary data from the Central Statistics Agency (BPS) and employing multiple linear regression in SPSS to uncover meaningful patterns. The results show that both economic growth and unemployment significantly affect poverty. The open unemployment rate has the greatest influence, indicating that higher unemployment leads to higher poverty levels. Meanwhile, economic growth has not been inclusive, as the benefits of development have not been evenly distributed among different income groups. The study concludes that reducing poverty requires inclusive, pro-poor economic growth through employment creation, MSME empowerment, and economic diversification, to ensure that the benefits of economic progress are shared equitably and contribute to sustainable welfare improvements in Southeast Sulawesi Province.